Synthetic [CII] emission maps of a simulated molecular cloud in formation - Franeck, Annika; Glover, Simon; Klessen, Ralf S.; Pellegrini, Eric William (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. The C+ ion is an important coolant of interstellar gas, and so the [C ii] fine structure line is frequently observed in the interstellar medium. Howe